Superplasticity of friction stirred processed al 7075 - Teo, Elizabeth Shu Hui (2014)
Superplastic forming has posed a strong industrial attraction due to its forming ability of large intricate shapes with sheet metal in one operation. This phenomenon is assisted by the fine grain size possessed by the material placed in an environment with an elevated temperature.